An Exploratory Factor Analysis (EFA) in determining dimensions of integrated and holistic Islamic education among Kuliyyah of Education - Surajudeen, Ahmad Tijani; Awang Mat , Muhamad Zahiri; Alizadegani , Faetmeh (Faculty of Education, University of Malaya, 2015)
The recent studies have shown that the Islamic education system is stagnant among Muslim students because it lacks critical thinking skills (Hashim and Hussien, 2003). The First World Conference on Muslim Education held in Makkah in 1977 recommended integrated and holistic Islamic education as an alternative education paradigm among Muslims in order to address problems inherent with Islamic education (Conference Book, 1977). Few studies have been conducted to empirically examine the underlining factors determining integrated and holistic educational system. The primary objective of this study is to validate the major components of integrated and holistic Islamic educational system as proposed in the resolution of the First World Conference on Muslim Education held in Makkah in 1977 by using explanatory factor analysis (EFA). The research design in the present study is quantitative. The population of the study was undergraduate and postgraduate students at the Kuliyyah of Education, International Islamic University Malaysia (IIUM). The total numbers of 121 respondents among undergraduate and postgraduate students at the Kuliyyah of Education (IIUM) were selected as a sample of this paper. The respondents were requested to respond to a-three-page survey questionnaire. The study validates the factors structure of integrated and holistic Islamic education using SPSS version 16.0. The exploratory factor analysis (EFA) was employed for data analysis in order to determine the numbers of factors or components of integrated and holistic Islamic education. From the Exploratory Factor Analysis (EFA), the findings from screen plot have identified three factors while seven (7) factors have been identified based on the initial eigenvalues and percentage variance of factors that orthogonally rotated. Both factors from screen plot and factors that orthogonally rotated were in line with the theoretical basis of this paper. The findings from this study would provide insightful information to the curriculum designers and lecturers of Islamic education and Islamization of knowledge at the Institute of Education, IIUM to enhance the content using integrated and holistic approach.